2019
DOI: 10.1080/13621718.2018.1521068
|View full text |Cite
|
Sign up to set email alerts
|

Projection friction stir spot welding: a pathway to produce strong keyhole-free welds

Abstract: This paper introduces a novel facile method, called projection friction stir spot welding, to produce a keyhole-free friction stir welds based on a pinless tool method involving using a specially designed projection on the surface of the backing anvil. The projection plays two key roles contributing to the bonding mechanism and the joint strength: (i) encouraging the material flow perpendicular to the joint interface and (ii) bending the joint interface at the edge of the projection. The process enables pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, the joining efficiency of aluminium alloys is still facing considerable challenges. To move towards efficient manufacturing and to reduce electrical energy consumption and costs, welding technology has to be carefully selected and optimised [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the joining efficiency of aluminium alloys is still facing considerable challenges. To move towards efficient manufacturing and to reduce electrical energy consumption and costs, welding technology has to be carefully selected and optimised [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance spot welding (RSW) continues to remain a predominant body-in-white process in the automotive industry. However, high electrical energy consumption, as well as the tendency to degrade the electrodes, make this process too expensive for joining aluminium and its alloys [ 2 , 12 , 13 ]. This has motivated researchers, especially in the automotive industry, to seek novel or improved low-energy consumption joining processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturers in the automotive industry face an increasingly competitive environment [1]. Remarkably, resistance spot welding (RSW) is a critical manufacturing technology in such sector [2,3], since its high speed and adaptability for automation render it suitable for mass production [4].The number of RSW joints per vehicle is very high (around 5000 according to Xia et al [5]), and there can be significant variability in the quality of each of them due to the fact that RSW is a complex process [6,7]; more precisely, the heat generated by an electrical current has to be substantial enough to promote local melting and the formation of a weld nugget at the faying interface [8,9], while at the same time the amount of heat is influenced by the electrical conductivity of the materials to be joined and by their surface condition, as well as by the thermal conductivity of the electrodes that are water-cooled and act as heat sinks [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on FSSW of an Al alloy revealed that a pinless tool can form a good joint without the hook interface and keyholes [ 13 , 14 , 15 ]. Mousavizade et al applied pinless FSSW on a mild steel sheet with a projection-backing anvil and proved that the technique provided high tensile strength because of the absence of keyholes [ 16 ]. Although the pinless tool approach during FSSW is a promising way to achieve a high-quality joint of AHSS, the published research on this subject is still limited.…”
Section: Introductionmentioning
confidence: 99%